Nanomedicines modulating tumor immunosuppressive cells to enhance cancer immunotherapy - Zhu, Yuefei (Acta Pharm Sin B, 2020)
Cancer immunotherapy has veered the paradigm of cancer treatment. Despite recent advances in immunotherapy for improved antitumor efficacy, the complicated tumor microenvironment (TME) is highly immunosuppressive, yielding both astounding and unsatisfactory clinical successes. In this regard, clinical outcomes of currently available immunotherapy are confined to the varied immune systems owing in large part to the lack of understanding of the complexity and diversity of the immune context of the TME. Various advanced designs of nanomedicines could still not fully surmount the delivery barriers of the TME. The immunosuppressive TME may even dampen the efficacy of antitumor immunity. Recently, some nanotechnology-related strategies have been inaugurated to modulate the immunosuppressive cells within the tumor immune microenvironment (TIME) for robust immunotherapeutic responses. In this review, we will highlight the current understanding of the immunosuppressive TIME and identify disparate subclasses of TIME that possess an impact on immunotherapy, especially those unique classes associated with the immunosuppressive effect. The immunoregulatory cell types inside the immunosuppressive TIME will be delineated along with the existing and potential approaches for immunosuppressive cell modulation. After introducing the various strategies, we will ultimately outline both the novel therapeutic targets and the potential issues that affect the efficacy of TIME-based nanomedicines.